2022
DOI: 10.3389/fphys.2022.1051529
|View full text |Cite
|
Sign up to set email alerts
|

Potential physiological responses contributing to the ergogenic effects of acute ischemic preconditioning during exercise: A narrative review

Abstract: Ischemic preconditioning (IPC) has been reported to augment exercise performance, but there is considerable heterogeneity in the magnitude and frequency of performance improvements. Despite a burgeoning interest in IPC as an ergogenic aid, much is still unknown about the physiological mechanisms that mediate the observed performance enhancing effects. This narrative review collates those physiological responses to IPC reported in the IPC literature and discusses how these responses may contribute to the ergoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 144 publications
1
5
0
Order By: Relevance
“…The threshold to pain perception likely reflects the responsiveness of nociceptors to noxious stimuli (Smith & Lewin, 2009), with an increased pain threshold mediated by a desensitisation of the nociceptors. Based on the current evidence, it is unlikely that IPC desensitises the group III/IV afferent nociceptors as previously postulated (De Oliveira Cruz et al, 2017; O’Brien & Jacobs, 2022). However, if a conditioned pain modulation effect was present (as suggested by a reduction in pain during the IPC) then it would be expected that there would also be an increase in pain threshold as is observed with typical conditioned pain modulation paradigms (Kennedy et al, 2016).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The threshold to pain perception likely reflects the responsiveness of nociceptors to noxious stimuli (Smith & Lewin, 2009), with an increased pain threshold mediated by a desensitisation of the nociceptors. Based on the current evidence, it is unlikely that IPC desensitises the group III/IV afferent nociceptors as previously postulated (De Oliveira Cruz et al, 2017; O’Brien & Jacobs, 2022). However, if a conditioned pain modulation effect was present (as suggested by a reduction in pain during the IPC) then it would be expected that there would also be an increase in pain threshold as is observed with typical conditioned pain modulation paradigms (Kennedy et al, 2016).…”
Section: Discussionsupporting
confidence: 72%
“…However, in the last decade, IPC has been found to enhance exercise performance (Crisafulli et al, 2011;De Groot et al, 2010;Santos de Oliveira Cruz et al, 2015), exercise recovery (Franz et al, 2018;Page et al, 2017;Patterson et al, 2021) and post-operative outcomes (Memtsoudis et al, 2010(Memtsoudis et al, , 2014Pereira et al, 2016). Pain, which is defined as "an unpleasant sensory and emotional experience associated with, or resembling that associated with, actual or potential tissue damage" (Raja et al, 2020) is a common sensation that is experienced across these different physiological perturbations, and a reduction in pain perception may be one of the mechanisms which underpins the ergogenic effect of IPC (Astokorki & Mauger, 2017;Behrens et al, 2020;O'Brien & Jacobs, 2022;Pereira et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was more variation in the sham or control groups included in these studies. A sham procedure typically involves applying the cuff for the same duration of the IPC protocol but with a lower pressure applied, designed to mimic the IPC procedure and make the participants believe it is effective in a placebo effect ( O’Brien and Jacobs, 2022 ). Ten studies as shown in Table 2 included a sham (i.e., 20 mmHg) or control intervention group or crossover trial, resulting in a limited impact on blood flow.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the plasma concentration of an opioid neuropeptide such as beta-endorphin is thought to be released in response to stimulation of group III and group IV afferent fibers, activating the pain inhibitory pathways (13). Therefore, if ischemic preconditioning were to reduce the perception of fatigue and pain sensitivity, exercise performance might be augmented through attenuating fatigue development (25). In this study, there was evidence suggesting that pressure pain threshold increased after both ischemic preconditioning protocols relative to sham and control conditions, which has been used as an indirect marker of change in sensitivity of group III and group IV afferent fibers (1).…”
Section: Discussionmentioning
confidence: 99%